2020
DOI: 10.1038/s41598-020-63891-y
|View full text |Cite
|
Sign up to set email alerts
|

Different “metabolomic niches” of the highly diverse tree species of the French Guiana rainforests

Abstract: Tropical rainforests harbor a particularly high plant diversity. We hypothesize that potential causes underlying this high diversity should be linked to distinct overall functionality (defense and growth allocation, anti-stress mechanisms, reproduction) among the different sympatric taxa. In this study we tested the hypothesis of the existence of a metabolomic niche related to a species-specific differential use and allocation of metabolites. We tested this hypothesis by comparing leaf metabolomic profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 71 publications
3
24
0
Order By: Relevance
“…The huge diversity of specialized metabolites results from various metabolic pathways, in which variable combinations of precursor subunits are used, as well as from multi-member gene and enzyme families, multi-product enzymes, low substrate specificities of certain enzymes and various modifications of backbones (e.g., methylation, glycosylation) within substance classes [ 4 , 33 , 34 ]. Across plant species, the metabolite richness differs pronouncedly, as shown in the present study and in other studies for herbs and trees [ 9 , 13 , 35 ]. We cannot rule out that the variability in the metabolite numbers is partly related to different leaf matrices affecting metabolite extraction and detection.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The huge diversity of specialized metabolites results from various metabolic pathways, in which variable combinations of precursor subunits are used, as well as from multi-member gene and enzyme families, multi-product enzymes, low substrate specificities of certain enzymes and various modifications of backbones (e.g., methylation, glycosylation) within substance classes [ 4 , 33 , 34 ]. Across plant species, the metabolite richness differs pronouncedly, as shown in the present study and in other studies for herbs and trees [ 9 , 13 , 35 ]. We cannot rule out that the variability in the metabolite numbers is partly related to different leaf matrices affecting metabolite extraction and detection.…”
Section: Discussionsupporting
confidence: 83%
“…When comparing the chemical composition among species, their phylogenetic relatedness should be taken into account, similarly as is done in comprehensive biodiversity studies [ 11 , 12 ]. Phylogenetic imprints in the metabolome are a result of past and current environmental factors that shape the metabolic composition of plants [ 4 ], leading to species-specific metabolomic niches [ 13 ]. Ecometabolomics tools are increasingly used to explore such taxon-related differences but also to uncover species-specific responses to certain environmental conditions [ 9 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, total phenolic concentrations in birch ( Betula pendula ) leaves increased with plot diversity level (Poeydebat et al, 2020). So far, untargeted metabolomic approaches have been mostly used to quantify chemical diversity related to phylogenetic distances in large tropical tree genera (Endara et al, 2015, Salazar et al, 2018, Sedio, 2017), chemical diversity within canopies (Sedio et al, 2019, Sedio et al, 2017, Wiggins et al, 2016), induced responses, or variation in leaf metabolomes among seasons (Gargallo-Garriga et al, 2020). To our knowledge, none of these studies considered the effect of tree diversity levels as a driver of variation in tree metabolomes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified associations between species assemblages and habitat conditions in tropical rainforests [50][51][52][53], such as variations in leaf properties (parental material, drainage), leaf nutrient availability [14] and topography (slope steepness and orientation, margins with water courses), that are consistent with niche theory. Extensions of the classical ecological niche hypothesis, such as the biogeochemical niche hypothesis, claim that species tend to reach an optimal chemical composition that is linked to a singular optimal function (homeostasis) and allows niche occupation [54][55][56][57][58]. Thus, this study provides evidence for the use of a fundamental resource, such as the P, in the characterization of species niche space.…”
Section: Discussionmentioning
confidence: 68%